Respect for human dignity as 'substantive basic norm'. Issue 1 (31st January 2014) - Neal, Mary
Abstract: The idea of 'human dignity' is, notoriously, as ambiguous as it is compelling. Notwithstanding the absence of any clear or settled definition of human dignity, either in the abstract or in terms of what it means in practice, it is an idea which takes pride of place in international legal documents, in judicial reasoning, and in scholarship across a range of disciplines, where it seems, particularly in recent years, to have become the focus for an explosion of academic interest and an accompanying proliferation of literature. Much of the existing literature attempts to uncover the meaning, or multiple meanings, of 'human dignity', focusing on the uncertainty surrounding the substance or content of the idea and trying to compose a catalogue of use-types. In this paper, my primary aim will be to address another type of uncertainty, namely uncertainty about the role, function or status within legal frameworks of the 'dignity norm' – the norm requiring respect for human dignity. I want to explore several possibilities: first, that the dignity norm is simply a proxy for respect for autonomy; second, that it is a right in the sense that we can speak of a specific 'right to have dignity respected'; and third, that it is a legal principle. Having problematised each of these in turn, I will contend that the function of the dignity norm is best captured by describing it as the 'substantive basic norm' of the legal systems wherein it appears.